IMPLEMENTASI IT PADA SISTEM INFORMASI AKUNTANSI PT. MASTER GRAFIKA JAKARTA - . Normah (JURNAL TEKNIK KOMPUTER AMIK BSI, 2018)
PT. Master Grafika is a private company engaged in services and trade in the world of printing. PT. Master Grafika still uses the system manually by using Microsoft Excel application in accounting data processing, so in the process of presenting financial information and data search takes a long time. Along with the development of the wheels of PT. Master Graphics requires improvements in its business data management system, making changes from manual recording using Microsoft Excel to more automated. To support the smoothness of the presentation of financial statements, companies need an accounting application system such as by using accounting based software, Zahir Accounting, there are several advantages that are additionally reliable and facilitate users in accounting data processing, Zahir application also has integrated facilities and highly competitive, friendly language equipped with multi languages and data security, the resulting report not only be a financial report but also a business and financial analysis, so that PT. Master Grafika can easily provide financial reports quickly and accurately.